ANALISIS JURIDIS TINDAK PIDANA PENYEROBOTAN TANAH DI KOTA MAKASSAR: JURIDICAL ANALYSIS OF CRIMINAL ACTS OF LAND APPLICATION IN MAKASSAR CITY - Rahma, Rahma; Makkawaru, Zulkifli; Zubaidah, Siti (Faculty Of Law Bosowa University, 2022)
This study aims to determine the elements of the crime of land grabbing as evidenced in the decision Number 315/Pid.B/2020/Pn.Mks and to determine the judge's legal considerations in passing the decision Number 315/Pid.B/2020/Pn.Mks The research method used is qualitative legal research. The types and sources of data consist of primary data in the form of laws and regulations, Circular Letters of the Supreme Court and Court Decisions and secondary legal materials consisting of books, articles and journals related to this research. The entire legal material is collected in a structured systematic manner using qualitative measures and presented in a descriptive analysis. The results of the study indicate that the elements of the crime of land grabbing have been fulfilled in Article 167 Paragraph (1) but the act is not a criminal act and the judge's consideration in passing a acquittal is based on this case not including a crime but civil law, but every the judge's decision that renders the decision must be followed by sufficient considerations, both juridical considerations and sociological considerations.